Pengaruh Perputaran Piutang, Perputaran Kas, Perputaran Persediaan Terhadap Profitabilitas Perusahaan (Pada Sub Sektor Industri Barang Dan Konsumsi Yangterdaftar Dibursa Efek Indonesia Periode 2016-2017) - Enny Arita (CV. ITTC INDONESIA, 2023)
Profitability is the company's ability to earn profits or profits. Some factors that can affect profitability in companies are financial ratios. The purpose of this study was to determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on profitability in consumer goods industry sector companies listed on the Indonesia Stock Exchange in the period 2016-2020. The population in this study uses the consumer goods industry sector, the total population in this study were 54 consumer goods industry companies. The technique used in sampling was purposive sampling, with a sample of 35 consumer goods industry companies. The data used in this research is secondary data. The analysis model used to solve problems in this study is multiple linear regression with a significant level of 5%. Based on the results of the analysis found that cash turnover has a positive effect on profitability, receivable turnover has a positive effect on profitability, and inventory turnover has a positive effect on profitability..